On the move: exploring Inuit and non-Inuit health service providers’ perspectives about youth, family and community participation in care in Nunavik - Sarah Louise Fraser; Louise Moulin; Dominique Gaulin; Jennifer Thompson (BMC Health Services Research, 2021)
Abstract Background Literature about participation in health and social services suggests that youth, and more specifically Indigenous youth, are difficult to engage within health and social services. Youth are less likely to access services or to actively participate in decision-making regarding their personal care. Service providers play a crucial role in engaging youth based on the ways in which they seek, establish, and maintain relationships with youth and their families. The way in which providers engage with youth will depend on various factors including their own perceptions of the roles and relationships of the various people involved in youth’s lives. In this article, we analyze health and social service providers’ perspectives, experiences and expectations regarding the roles of Indigenous youth, families and community in care settings in Nunavik, Quebec. Methods Using a snowball sampling approach, we recruited 58 interview participants (39 non-Inuit and 19 Inuit), including psychiatrists, general practitioners, nurses, social workers, school principals, teachers, student counsellors, representatives of local committees, and police officers. The interviews focused on three broad areas: 1) participants’ current and past positions and roles; 2) participants’ perceptions of the clientele they work with (youth and their families); and 3) participants’ understandings of how collaboration takes place within and between services and the community. We conducted inductive applied thematic analyses and then analyzed the interview transcripts of Inuit and non-Inuit participants separately to explore the similarities and differences in perceptions based on positionality. Results We organized the findings around three themes: I) the most commonly described interventions, II) different types of challenges to and within participation; and III) what successful participation can look like according to service providers. Participants identified the challenges that families face in moving towards services as well as the challenges that services providers face in moving towards youth and families, including personal, organizational and historical factors. Conclusion We adopt a critical lens to reflect on the key findings in order to tease out points of tension and paradoxes that might hinder the participation of youth and families, specifically in a social context of decolonization and self-governance of services.